Solid electrolyte material and preparation method thereof, solid electrolyte membrane and battery
By coating amide compounds on the surface of sulfide electrolytes and combining specific processes to prepare core-shell structured electrolyte materials and membranes, the processing difficulties of sulfide electrolytes in high dew point environments were solved, the air stability and conductivity of the battery were improved, and battery performance with high capacity and long cycle life was achieved.
Patent Information
- Application Number
- CN202511042874.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-10-14
AI Technical Summary
Liquid electrolyte lithium-ion batteries lack safety and energy density, and sulfide solid electrolytes are difficult to process in high dew point environments and the material conductivity decreases, affecting battery performance.
A solid electrolyte material with a core-shell structure is used, with the core being a sulfide electrolyte and the outer layer being an amide compound coating. It is prepared by mixing, pressing, heat treatment and crushing, and the electrolyte membrane is prepared by coating a mixed slurry of ionic liquid, lithium salt and binder.
The air stability and electrical conductivity of the solid electrolyte material are improved, ensuring the charge and discharge performance of the battery and achieving high capacity and long cycle life.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular to a solid-state electrolyte material, a preparation method thereof, a solid-state electrolyte film and a battery. BACKGROUND
[0002] Liquid electrolyte lithium ion batteries face bottlenecks in safety and energy density, and are difficult to meet the application requirements of electric vehicles and energy storage. In recent years, lithium ion all-solid-state batteries have made great progress and are expected to solve the safety problems of flammable and explosive liquid electrolytes. Among them, sulfide solid-state electrolytes have high ionic conductivity and processability, and are more suitable for preparing high-energy-density battery cells. However, sulfide solid-state electrolytes are extremely sensitive to water and need to be processed and film-formed in a high dew point environment, greatly increasing the processing difficulty and cost of wet film formation. Coating with hydrophobic materials can effectively improve the air stability of the electrolyte, but at the same time, it will cause the conductivity of the material to decrease and thus adversely affect the performance of the battery.
[0003] Therefore, the present application is proposed. SUMMARY
[0004] One object of the present application is to provide a solid-state electrolyte material that can significantly improve air stability while ensuring that the conductivity meets the performance requirements of battery cell preparation.
[0005] Another object of the present application is to provide a preparation method of a solid-state electrolyte material, which can significantly improve the air stability of the solid-state electrolyte material through the cooperation of each step, while ensuring that the conductivity does not affect the charge and discharge performance of the battery cell.
[0006] Another object of the present application is to provide a preparation method of a solid-state electrolyte film, which is simple and easy to implement.
[0007] Another object of the present application is to provide a solid-state electrolyte film that has excellent air stability while ensuring that the appropriate conductivity meets the requirements of battery cell preparation.
[0008] Another object of the present application is to provide a battery that has high capacity and long cycle characteristics.
[0009] In order to achieve the above objects of the present application, the following technical solutions are adopted: A solid-state electrolyte material, the solid-state electrolyte material has a core-shell structure, the core-shell structure includes an inner core and a coating layer arranged on the surface of the inner core, the inner core includes a sulfide electrolyte, and the coating layer includes an amide compound.
[0010] In some embodiments, the amide compound includes at least one of undecanamide, dodecanamide, tridecanamide, bromoundecanamide and N-cyclohexylhexanamide.
[0011] In some embodiments, the sulfide electrolyte comprises Li x M y P z S w Q n at least one of aLi2S-bP2S5 and Li2S-SiS2, wherein M comprises at least one of Si, Ge and Sn, Q comprises at least one of F, Cl, Br and I, x+4y+5z=2w+n, 2≤x≤11, 0≤y≤2, 0≤z≤3, 3≤w≤13, a / b is (7~8):(2~3).
[0012] In some embodiments, the D50 particle size of the sulfide electrolyte is 0.2~20μm.
[0013] In some embodiments, the thickness of the coating layer is 5~30nm.
[0014] A preparation method of the solid-state electrolyte material as described above, comprising the following steps: mixing and processing the sulfide electrolyte and the amide compound, and performing pressing treatment to obtain a pressed body; performing heat treatment, cooling treatment and crushing treatment on the pressed body to obtain the solid-state electrolyte material.
[0015] In some embodiments, the mass ratio of the sulfide electrolyte and the amide compound is (95~98):(2~5).
[0016] In some embodiments, the mixing treatment comprises grinding treatment, the rotation speed of the grinding treatment is 200~500rpm, and the grinding treatment time is 0.5~2h.
[0017] In some embodiments, the pressure of the pressing treatment is 50~200MPa.
[0018] In some embodiments, the temperature of the heat treatment is 50~350℃, and the heat treatment time is 10~120min.
[0019] In some embodiments, the cooling treatment is cooled to room temperature.
[0020] A preparation method of a solid-state electrolyte film, comprising the following steps: obtaining a mixed slurry of the solid-state electrolyte material, ionic liquid, lithium salt, binder and solvent.
[0021] coating the mixed slurry to the surface of a base film to obtain the solid-state electrolyte film after drying.
[0022] In some embodiments, the solid-state electrolyte material has a mass content of 90-95% in the solid-state electrolyte film.
[0023] In some embodiments, the mass ratio of the ionic liquid, the lithium salt and the binder is (1-2):1:1.
[0024] In some embodiments, the ionic liquid comprises at least one of choline chloride, betaine, tetrabutylammonium chloride, tetraheptylammonium chloride, tetraoctylammonium bromide, cetyltrimethylammonium bromide and 1-ethyl-3-methylimidazolium chloride.
[0025] In some embodiments, the lithium salt comprises at least one of lithium hexafluorophosphate, lithium bisfluorosulfonylimide, lithium bis(trifluoromethanesulfonyl)imide and lithium tetrafluoroborate.
[0026] In some embodiments, the binder comprises at least one of PVDF, PVDF-HFP, styrene elastomer, nitrile rubber, hydrogenated nitrile rubber, vinyl acetate and polyvinyl butyral.
[0027] In some embodiments, the solvent comprises at least one of anisole, ethyl acetate, butyl butyrate, dimethyl ether, diethylene glycol dimethyl ether, N-methylpyrrolidone, mesitylene and xylene.
[0028] In some embodiments, the mixed slurry is obtained by mixing the ionic liquid, the lithium salt and the binder and the solvent, and then mixing and grinding with the solid-state electrolyte material.
[0029] In some embodiments, the mixed slurry has a solid content of 40-60%.
[0030] In some embodiments, the base film comprises at least one of PET film, aramid film and aluminum foil. The thickness of the base film is 10-50 µm. In some embodiments, the drying temperature is 70-95 °C.
[0031] A solid-state electrolyte film prepared by the method for preparing a solid-state electrolyte film.
[0032] A battery comprising the solid-state electrolyte material, or the solid-state electrolyte film prepared by the method for preparing a solid-state electrolyte film, or the solid-state electrolyte film.
[0033] In some embodiments, the thickness of the solid-state electrolyte film is 25-120 µm.
[0034] Compared with the prior art, the present application has the following advantages: (1) The solid-state electrolyte material of the present application can effectively improve the air stability of the solid-state electrolyte material by setting the coating layer containing the amide compound on the surface of the sulfide electrolyte, while ensuring that it has suitable electrical conductivity without affecting the performance of the battery during charging and discharging.
[0035] (2) The preparation method of the solid-state electrolyte material of the present application sequentially mixes and processes the sulfide electrolyte and the amide compound, and then performs pressing treatment, heat treatment and crushing treatment. The amide compound is solid at room temperature, and melts into liquid after heat treatment. The material can uniformly coat the sulfide electrolyte, and the solid form is restored after cooling, which is easier to store. This method can improve the coating effect of the amide compound, and thus obtain a solid-state electrolyte material with high air stability and electrical conductivity meeting the performance requirements of the battery.
[0036] (3) The preparation method of the solid-state electrolyte film of the present application is simple and easy to operate. The mixed slurry of the solid-state electrolyte material, ionic liquid, lithium salt, binder and solvent is coated on the surface of the base film and dried. The solid-state electrolyte material and the ionic liquid have strong intermolecular forces (hydrogen bonds), which can reduce the melting point of the mixture and facilitate the dissolution of the lithium salt. At a higher test temperature, the electrolyte pores can be filled, the cell polarization can be reduced, and the cell performance can be improved. This method can obtain a solid-state electrolyte film with high air stability, while ensuring that the electrical conductivity meets the requirements of battery preparation.
[0037] (4) The solid-state electrolyte film of the present application has excellent air stability while ensuring that the appropriate electrical conductivity meets the requirements of battery preparation.
[0038] (5) The battery of the present application has high capacity and long cycle life. DETAILED DESCRIPTION
[0039] The embodiments of the present application will be described in detail below with reference to the examples, but those skilled in the art will understand that the following examples are only for illustration of the present application and should not be regarded as limiting the scope of the present application. If the specific conditions are not specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are used. If the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be obtained by purchase.
[0040] According to one aspect of the present application, the present application relates to a solid-state electrolyte material having a core-shell structure, the core-shell structure comprising an inner core and a coating layer provided on the surface of the inner core, the inner core comprising a sulfide electrolyte, and the coating layer comprising an amide compound.
[0041] The solid electrolyte material of the present application can effectively improve the air stability of the solid electrolyte material by arranging the coating layer containing the amide compound on the surface of the sulfide electrolyte, while ensuring that the solid electrolyte material has suitable electrical conductivity without affecting the performance of the battery.
[0042] In some embodiments, the amide compound includes at least one of undecanamide, dodecanamide, tridecanamide, bromoundecanamide, and N-cyclohexylhexanamide. The amide compound of the present application can be a combination of one or more of the above, such as a combination of undecanamide and dodecanamide, a combination of tridecanamide and bromoundecanamide, a combination of tridecanamide, bromoundecanamide, and N-cyclohexylhexanamide, etc. The amide compound of the present application is conducive to ensuring hydrophobicity and improving the air stability of the solid electrolyte material.
[0043] In some embodiments, the sulfide electrolyte includes Li x M y P z S w Q n , at least one of aLi2S-bP2S5 and Li2S-SiS2, wherein M includes at least one of Si, Ge, and Sn, Q includes at least one of F, Cl, Br, and I, x+4y+5z=2w+n, 2≤x≤11 (such as 2, 5, 7, 10, or 11, etc.), 0≤y≤2 (such as 0.1, 0.2, 0.5, 1, 1.5, or 2, etc.), 0≤z≤3 (such as 0.1, 0.5, 1, 1.5, 2, or 3, etc.), 3≤w≤13 (such as 3, 5, 8, 10, or 13, etc.), and a / b is (7~8):(2~3), such as 7:3, 7.5:2.5, 8:2, etc. The sulfide electrolyte of the present application has good electrical conductivity.
[0044] In some embodiments, the D50 particle size of the sulfide electrolyte is 0.2~20μm, such as 0.2μm, 0.5μm, 1μm, 2μm, 3μm, 5μm, 10μm, 12μm, 15μm, or 20μm, etc. The sulfide electrolyte of the present application has a suitable D50 particle size, thereby ensuring the coating effect of the coating layer and ensuring the conductivity and stability of the solid electrolyte material.
[0045] In some embodiments, the thickness of the coating layer is 5~30nm, such as 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, etc. The coating layer of the present application has a suitable thickness, which can ensure the improvement effect of the air stability of the solid electrolyte material, while ensuring that the electrical conductivity meets the performance requirements of the battery cell.
[0046] According to another aspect of the present application, the present application also relates to a preparation method of the solid-state electrolyte material as described above, comprising the following steps: The sulfide electrolyte and the amide compound are mixed and processed and pressed to obtain a pressed body; the pressed body is subjected to heat treatment, cooling treatment and crushing treatment to obtain the solid-state electrolyte material.
[0047] The preparation method of the solid-state electrolyte material of the present application sequentially processes the sulfide electrolyte and the amide compound through mixing, pressing, heat treatment and crushing, the amide compound is solid at room temperature, and is molten into liquid after heat treatment, which can realize uniform coating of the material on the sulfide electrolyte, and the solid form is restored after cooling, which is easier to store; the method can improve the coating effect of the amide compound, and thus obtain a solid-state electrolyte material with high air stability and electrical conductivity meeting the performance requirements of the battery cell.
[0048] In some embodiments, the mass ratio of the sulfide electrolyte and the amide compound is (95-98):(2-5), such as 95:5, 96:4, 97:3, 98:2, etc. The present application adopts a suitable mass ratio of the sulfide electrolyte and the amide compound, which is more conducive to ensuring that the coating layer has a suitable thickness and coating effect, and is conducive to the performance of electrical conductivity and stability. If the mass ratio of the sulfide electrolyte and the amide compound is too large, the coating layer is too thin, the coating rate is too low, and the interface improvement effect is not obvious; if the mass ratio of the sulfide electrolyte and the amide compound is too small, the coating layer is too thick, which is also not conducive to the performance of the solid-state electrolyte material.
[0049] In some embodiments, the mixing process includes grinding treatment, and the rotation speed of the grinding treatment is 200-500 rpm, such as 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm or 500 rpm, etc. The grinding treatment time is 0.5-2 h, such as 0.5 h, 1 h or 2 h, etc. The present application adopts suitable mixing conditions to ensure uniform mixing of the materials and suitable particle size, which is conducive to the subsequent coating effect.
[0050] In some embodiments, the pressure of the pressing treatment is 50-200 MPa, such as 50 MPa, 60 MPa, 80 MPa, 100 MPa, 120 MPa, 150 MPa, 160 MPa, 180 MPa, 200 MPa, etc. The present application adopts suitable pressing conditions to form a pressed body with a suitable structure, which is conducive to the thickness of the heat treatment and the coating effect of the molten amide compound.
[0051] In some embodiments, the temperature of the heat treatment is 50-350℃, such as 50℃, 100℃, 150℃, 200℃, 250℃, 300℃, 350℃, etc. The time of the heat treatment is 10-120min, such as 10min, 20min, 30min, 40min, 60min, 80min, 100min, 120min, etc. The present application adopts appropriate heat treatment conditions to ensure the melting of the amide compound to form a uniform coating layer.
[0052] In some embodiments, the cooling treatment is cooled to room temperature, and the amide compound forms a solid phase coating layer uniformly coated on the surface of the sulfide electrolyte.
[0053] According to one aspect of the present application, the present application also relates to a preparation method of a solid-state electrolyte film, comprising the following steps: Obtaining a mixed slurry of the solid-state electrolyte material, ionic liquid, lithium salt, binder and solvent.
[0054] Coating the mixed slurry to the surface of the base film, and drying to obtain the solid-state electrolyte film.
[0055] The preparation method of the solid-state electrolyte film of the present application is simple and easy to operate, and the mixed slurry of the solid-state electrolyte material, ionic liquid, lithium salt, binder and solvent is coated to the surface of the base film and dried. The solid-state electrolyte material and the ionic liquid have strong intermolecular forces (hydrogen bonds) between them, which can reduce the melting point of the mixture of the two and is conducive to promoting the dissolution of the lithium salt, filling the electrolyte pores at a higher test temperature, reducing the polarization of the battery cell, and improving the performance of the battery cell. The method can obtain a solid-state electrolyte film with high air stability while ensuring the electrical conductivity to meet the requirements of battery cell preparation.
[0056] In some embodiments, the mass content of the solid-state electrolyte material in the solid-state electrolyte film is 90%-95%, such as 90%, 91%, 92%, 93%, 94% or 95%, etc. In some embodiments, the mass ratio of the ionic liquid, the lithium salt and the binder is (1-2):1:1, such as 1:1:1, 1.5:1:1, 2:1:1. In the solid-state electrolyte film of the present application, the solid-state electrolyte material, ionic liquid, lithium salt and binder have an appropriate ratio, and each component plays a role in coordination, which is more conducive to ensuring the air stability and electrochemical performance of the solid-state electrolyte film.
[0057] In some embodiments, the ionic liquid comprises at least one of choline chloride, betaine, tetrabutylammonium chloride, tetraheptylammonium chloride, tetraoctylammonium bromide, cetyltrimethylammonium bromide, and 1-ethyl-3-methylimidazolium chloride, such as a combination of choline chloride and betaine, a combination of tetrabutylammonium chloride, tetraheptylammonium chloride, and tetraoctylammonium bromide, etc. The above ionic liquid of the present application can improve the ion conduction ability and enhance the electrochemical stability.
[0058] In some embodiments, the lithium salt comprises at least one of lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonylimide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), such as a combination of lithium hexafluorophosphate and lithium bisfluorosulfonylimide, a combination of lithium bis(trifluoromethanesulfonyl)imide and lithium tetrafluoroborate, etc. The above suitable lithium salt of the present application can improve the ionic conductivity.
[0059] In some embodiments, the binder comprises at least one of PVDF, PVDF-HFP, styrene elastomer, nitrile rubber, hydrogenated nitrile rubber, vinyl acetate, and polyvinyl butyral; wherein the styrene elastomer comprises at least one of SEBS, SEEPS, and SBR.
[0060] In some embodiments, the solvent comprises at least one of anisole, ethyl acetate, butyl acetate, dimethyl ether, diethylene glycol dimethyl ether, N-methylpyrrolidone, mesitylene, and xylene, such as a combination of anisole and ethyl acetate, a combination of butyl acetate and dimethyl ether, etc. The above solvent of the present application can well dissolve the dispersed materials to obtain a uniform mixture.
[0061] In some embodiments, the mixed slurry is obtained by uniformly mixing the ionic liquid, the lithium salt, the binder, and the solvent, and then mixing and grinding the solid-state electrolyte material. In some embodiments, the grinding comprises ball milling at a rotation speed of 200-400 rpm for 20-50 min. After mixing the ionic liquid and the lithium salt, the lithium ions are dissociated, similar to a liquid electrolyte, and the ion transmission rate is accelerated, especially under high temperature conditions, thus improving the conductivity. The amide compound of the solid-state electrolyte material has good hydrophobicity, while the ionic liquid and the lithium salt have strong hydrophilicity. The above feeding sequence can significantly improve the air stability of the material and ensure the electrochemical performance of the electrolyte film.
[0062] In some embodiments, the mixed slurry has a solid content of 40% to 60%, such as 40%, 45%, 50%, 55%, 60%, or the like. The mixed slurry of the present application has a suitable solid content to facilitate subsequent drying and form a solid-state electrolyte film with excellent mechanical and electrochemical properties. If the solid content of the mixed slurry is too low, solvent shrinkage during drying can cause cracking, and if the solid content of the mixed slurry is too high, the slurry has too poor flowability, affecting the coating effect and deteriorating the performance of the coating layer.
[0063] In some embodiments, the base film comprises a combination of one or more of a PET film, an aramid film, and an aluminum foil. The base film has a thickness of 10 to 50 µm, such as 10 µm, 20 µm, 30 µm, 50 µm, or the like. In some embodiments, the drying temperature is 70 to 95 °C, such as 70 °C, 80 °C, 90 °C, or 95 °C, or the like.
[0064] According to another aspect of the present application, the present application also relates to a solid-state electrolyte film prepared by the above-mentioned method for preparing a solid-state electrolyte film.
[0065] The solid-state electrolyte film of the present application has excellent air stability while ensuring suitable electrical conductivity to meet the requirements of battery preparation. According to another aspect of the present application, the present application also relates to a battery comprising the solid-state electrolyte material, or the solid-state electrolyte film prepared by the above-mentioned method for preparing a solid-state electrolyte film, or the solid-state electrolyte film.
[0066] The battery of the present application has high capacity and long cycle life.
[0067] In some embodiments, the solid-state electrolyte film has a thickness of 25 to 120 µm, such as 25 µm, 30 µm, 50 µm, 60 µm, 70 µm, 80 µm, 100 µm, or 120 µm, or the like. The solid-state electrolyte film of the present application has a suitable thickness to meet the needs of different batteries.
[0068] The present application will be further explained and described with reference to specific examples and comparative examples.
[0069] Example 1 A method for preparing a solid-state electrolyte material, comprising the following steps: 9.6 g of sulfide electrolyte Li6PS5Cl (D50 = 10 µm) was ball-milled with 0.4 g of an amide compound (undecanamide) at a speed of 400 rpm for 1 h, then pressed into a sheet under a pressure of 100 MPa, heated at 60 °C for 60 min, cooled to room temperature, and broken to obtain a solid-state electrolyte material coated with undecanamide, and the thickness of the coating layer was 20 nm.
[0070] A method for preparing a solid-state electrolyte film, comprising the following steps: 0.16g PVDF-HFP was added into 10g dimethyl ether solvent and stirred until completely dissolved, then 0.08g ionic liquid (betaine) and 0.08g LiFSI were added and stirred, followed by 6.08g of the solid-state electrolyte material described above, and the mixture was ball milled at 300rpm for 30min to obtain a uniform mixed slurry, the solid content of the mixed slurry was 50%, the mixed slurry was coated on an aluminum foil with a thickness of 12μm, and the solid-state electrolyte film was obtained by drying at 90℃, the thickness of the solid-state electrolyte film was 90μm.
[0071] Example 2 A method for preparing a solid-state electrolyte material, which is different from example 1 in that: The amide compound is dodecanamide and N-cyclohexylhexanamide, and the mass ratio is 3:1; the heating temperature is 250℃.
[0072] A method for preparing a solid-state electrolyte film, except that the solid-state electrolyte material of the present example is used, other conditions are the same as example 1.
[0073] Example 3 A method for preparing a solid-state electrolyte material, which is different from example 1 in that: The amide compound is tridecanamide, bromo-undecanamide and N-cyclohexylhexanamide, and the mass ratio is 2:1:1. The heating temperature is 300℃.
[0074] A method for preparing a solid-state electrolyte film, except that the solid-state electrolyte material of the present example is used, other conditions are the same as example 1.
[0075] Example 4 A method for preparing a solid-state electrolyte material, which is different from example 1 in that: Pressed into a sheet under a pressure of 200MPa.
[0076] A method for preparing a solid-state electrolyte film, except that the solid-state electrolyte material of the present example is used, other conditions are the same as example 1.
[0077] Example 5 A method for preparing a solid-state electrolyte material, which is different from example 1 in that: Pressed into a sheet under a pressure of 50MPa.
[0078] A method for preparing a solid-state electrolyte film, except that the solid-state electrolyte material of the present example is used, other conditions are the same as example 1.
[0079] Example 6 A method for preparing a solid-state electrolyte material, comprising the following steps: 9.8 g of sulfide electrolyte Li6PS5Cl (D50 = 5 μm) was mixed with 0.2 g of an amide compound (undecanamide) by ball milling at a rotation speed of 200 rpm for 2 h, and then pressed into a sheet under a pressure of 100 MPa. After heating at 60°C for 60 min, the sheet was cooled to room temperature and broken into pieces to obtain a solid-state electrolyte material coated with undecanamide, and the thickness of the coating layer was 10 nm.
[0080] A method for preparing a solid-state electrolyte film, comprising the following steps: After 0.3 g of PVDF-HFP was stirred in 10 g of dimethyl ether solvent until completely dissolved, 0.15 g of choline chloride and 0.15 g of LiFSI were added and stirred, followed by the addition of 6.08 g of the above solid-state electrolyte material. The mixture was ball milled at 400 rpm for 20 min to obtain a uniform mixed slurry, and the solid content of the mixed slurry was 40%. The mixed slurry was coated on an aluminum foil with a thickness of 12 μm, and the aluminum foil was dried at 95°C to obtain a solid-state electrolyte film with a thickness of 90 μm.
[0081] Example 7 A method for preparing a solid-state electrolyte material, comprising the following steps: 9.5 g of sulfide electrolyte Li6PS5Cl (D50 = 15 μm) was mixed with 0.5 g of an amide compound (undecanamide) by ball milling at a rotation speed of 500 rpm for 0.5 h, and then pressed into a sheet under a pressure of 100 MPa. After heating at 60°C for 60 min, the sheet was cooled to room temperature and broken into pieces to obtain a solid-state electrolyte material coated with undecanamide, and the thickness of the coating layer was 20 nm.
[0082] A method for preparing a solid-state electrolyte film, comprising the following steps: After 0.3 g of PVDF was stirred in 10 g of dimethyl ether solvent until completely dissolved, 0.15 g of choline chloride and 0.15 g of LiFSI were added and stirred, followed by the addition of 6.08 g of the above solid-state electrolyte material. The mixture was ball milled at 400 rpm for 20 min to obtain a uniform mixed slurry, and the solid content of the mixed slurry was 40%. The mixed slurry was coated on an aluminum foil with a thickness of 12 μm, and the aluminum foil was dried at 95°C to obtain a solid-state electrolyte film with a thickness of 90 μm.
[0083] Comparative Example 1 A method for preparing a solid-state electrolyte film, comprising the following steps: (1) 10 g of sulfide electrolyte Li6PS5Cl was ball milled at a rotation speed of 400 rpm for 1 h, and then pressed into a sheet under a pressure of 100 MPa. After heating at 60°C for 60 min, the sheet was cooled to room temperature and broken into pieces to obtain a solid-state electrolyte material.
[0084] (2) 0.16 g PVDF-HFP was added into 10 g dimethyl ether solvent and stirred until completely dissolved, then 7.68 g of the solid-state electrolyte material was added, and the mixture was ball milled at 300 rpm for 30 min to obtain a uniform mixed slurry. The solid content of the mixed slurry was 50%. The mixed slurry was coated on an aluminum foil, and the thickness of the aluminum foil was the same as in Example 1. The mixed slurry was dried at 90°C to obtain a solid-state electrolyte film. The thickness of the solid-state electrolyte film was the same as in Example 1.
[0085] Experimental Example I. Performance test of solid-state electrolyte material The initial ionic conductivity of the solid-state electrolyte material prepared in each example and comparative example was tested, as well as the ionic conductivity after being placed in a -50°C dew point environment for 30 min (referred to as after exposure experiment).
[0086] Ionic conductivity test: 100 mg of the above electrolyte material was placed in a test mold. After assembly, a pressure of 400 MPa was applied to the mold, and the test clamp was connected. The AC impedance was tested, and the intersection of the curve and the X-axis was the resistance Ω. After disconnecting the test line and removing the mold pressure, the thickness L of the electrolyte film and the area S of the electrolyte film were measured. The conductivity calculation method was: σ = L / (S·Ω).
[0087] The performance test results of the solid-state electrolyte material are shown in Table 1.
[0088] Table 1 Performance test results of solid-state electrolyte material
[0089] As can be seen from the above Table 1, the solid-state electrolyte of each example of the present application can effectively prevent moisture from corroding the electrolyte, has better air stability, and has higher ion conductivity retention rate after being exposed to a -50°C dew point environment.
[0090] II. Battery performance test results A 0.1 Ah soft package battery was obtained by compounding the above-mentioned electrolyte film with a dry positive electrode sheet (mass ratio NCM811:PTFE:VGCF = 92:4:4) and a micron silicon negative electrode sheet (mass ratio Si:PAA:CNT = 96:3:1). The above-mentioned battery was placed in a 45°C oven, and a 0.1C / 0.1C charge-discharge system was used to activate the battery, i.e., a 0.1C constant current was used to charge to 4.25V, and a 0.1C constant current was used to discharge to 2.5V. A 1C / 1C charge-discharge process was used to cycle 100 times, and the voltage range was 2.5~4.25V, i.e., a 1C constant current was used to charge to 4.25V, and a 1C constant current was used to discharge to 2.5V. The first discharge capacity and the capacity retention rate of the 100th charge-discharge were recorded.
[0091] Table 2 Battery performance test results
[0092] As shown in Table 2, the battery obtained from the solid electrolyte material of the present application has excellent initial discharge capacity and capacity retention rate.
[0093] The initial discharge capacity and capacity retention rate of the battery obtained from the solid electrolyte material of Comparative Example 1 are relatively low.
[0094] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present application, and are not intended to limit the present application; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that the technical solutions recorded in the foregoing examples can still be modified, or some or all of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A solid electrolyte material, characterized in that The solid electrolyte material has a core-shell structure, which includes a core and a coating layer arranged on the surface of the core. The core includes a sulfide electrolyte, and the coating layer includes an amide compound.
2. The solid electrolyte material according to claim 1, characterized in that Includes at least one of the following features (1) to (2): (1) The amide compound includes at least one of undecylamide, dodecylamide, tridecylamide, bromoundecylamide and N-cyclohexylhexylamide; (2) The sulfide electrolyte includes Li x M y P z S w Q n , at least one of aLi2S-bP2S5 and Li2S-SiS2, wherein M includes at least one of Si, Ge and Sn, Q includes at least one of F, Cl, Br and I, x+4y+5z=2w+n, 2≤x≤11, 0≤y≤2, 0≤z≤3, 3≤w≤13, and a / b is (7~8):(2~3).
3. The solid electrolyte material according to claim 1, characterized in that Includes at least one of the following features (1) to (2): (1) The D50 particle size of the sulfide electrolyte is 0.2~20μm; (2) The thickness of the coating layer is 5 to 30 nm.
4. The method for preparing a solid electrolyte material according to any one of claims 1 to 3, wherein: The following steps are involved: The sulfide electrolyte and the amide compound are mixed and pressed to obtain a pressed body; The pressed body is subjected to heat treatment, cooling treatment and crushing treatment to obtain a solid electrolyte material.
5. The method for preparing a solid electrolyte material according to claim 4, wherein: Contains at least one of the following features (1) to (5): (1) The mass ratio of the sulfide electrolyte to the amide compound is (95-98):(2-5); (2) The mixing process includes a grinding process, the rotation speed of the grinding process is 200-500 rpm, and the time of the grinding process is 0.5-2 hours; (3) The pressure of the pressing treatment is 50~200MPa; (4) The heat treatment temperature is 50-350°C, and the heat treatment time is 10-120 minutes; (5) The cooling process is to cool the device to room temperature.
6. A method for preparing a solid electrolyte membrane, characterized in that: The following steps are involved: Obtaining a mixed slurry of the solid electrolyte material, ionic liquid, lithium salt, binder and solvent according to any one of claims 1 to 3; The mixed slurry is coated on the surface of a base film and dried to obtain a solid electrolyte membrane.
7. The method for preparing a solid electrolyte membrane according to claim 6, wherein: Contains at least one of the following features (1) to (6): (1) The mass content of the solid electrolyte material in the solid electrolyte membrane is 90% to 95%; (2) The mass ratio of the ionic liquid, the lithium salt and the binder is (1-2):1:1; (3) The ionic liquid includes at least one of choline chloride, betaine, tetrabutylammonium chloride, tetraheptylammonium chloride, tetraoctylammonium bromide, hexadecyltrimethylammonium bromide and 1-ethyl-3-methylimidazolium chloride; (4) The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide and lithium tetrafluoroborate; (5) The binder comprises at least one of PVDF, PVDF-HFP, styrene elastomer, nitrile rubber, hydrogenated nitrile rubber, vinyl acetate and polyvinyl butyral; (6) The solvent includes at least one of anisole, ethyl acetate, butyl butyrate, dimethyl ether, diethylene glycol dimethyl ether, N-methylpyrrolidone, trimethylbenzene and xylene.
8. The method for preparing a solid electrolyte membrane according to claim 6, wherein: Contains at least one of the following features (1) to (4): (1) obtaining the mixed slurry, specifically comprising: uniformly mixing the ionic liquid, the lithium salt, the binder, and the solvent, and then mixing and grinding the mixed slurry with the solid electrolyte material; (2) The solid content of the mixed slurry is 40% to 60%; (3) The base film comprises at least one of a PET film, an aramid film, and an aluminum foil; the thickness of the base film is 10 to 50 μm; (4) The drying temperature is 70-95°C.
9. A solid electrolyte membrane, characterized in that The solid electrolyte membrane is prepared by the method for preparing the solid electrolyte membrane according to any one of claims 6 to 8.
10. A battery, characterized in that: A solid electrolyte material according to any one of claims 1 to 3, or a solid electrolyte membrane obtained by the method for preparing a solid electrolyte membrane according to any one of claims 6 to 8, or a solid electrolyte membrane according to claim 9; Preferably, the solid electrolyte membrane has a thickness of 25-120 μm.
Citation Information
Cited By
Water system-based composite electrolyte membrane and solid-state battery
CN120978230A
Solid electrolyte material and preparation method and application thereof
CN121748511A
A solid electrolyte material, its preparation method and application
CN121748511B
A modified sulfide solid electrolyte and a preparation method and application thereof
CN122619912A